Clinical profile and cerebrospinal fluid indices in children with complex febrile seizures - Dr. Amol Ramrao Suryavanshi; Dr. Sachin Bapurao Bodhgire; Dr. Rahul Digambarrao Anerao; Dr. Shilpa Pawar; Dr. Amit Tukaram Patil; Dr. Mugdha Paranjape (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Fever with seizure is the most common type of seizure occurring in children. A seizure is a common presentation for which a child may come to the emergency and may occur in up to 10% of children presenting to the emergency. Among all these seizures, Febrile seizures (FS) are the most common type of childhood seizures, affecting 2–5% of children older than 1 month and most commonly from 6 months–5 years old. The differential diagnosis of febrile seizure includes non-epileptic events or movements, provoked seizures following a central nervous system infection, and rare forms of genetic epilepsy in which seizures typically present with fever. Material and Methods: A hospital-based, prospective study conducted at the Department of Pediatrics, Government Medical College, and Hospital Aurangabad conducted from November 2018 to February 2020. Results: A total of 120 cases that presented with Complex Febrile Seizures (CFS) between six months to five years of age were included. Among them, 83 (69.1%) were male and 47 (30.9%) were female children. There were a total of 63 children in 6-12 months age, 32 in 12-24 months, and 25 in the above 12 months age group. Conclusion: In conclusion, it was found that age less than 1 year and male gender were the most significant risk factors for Complex Febrile Seizure in our area.